Efektivitas Penerapan Prinsip Negara Hukum dalam Kebijakan Desentralisasi di Indonesia - Helandri, Joni; Rinaldi Efendi; Rismanda Septri Giyanti; Bobi Susanto; Syefi Aulia Agustiani; Syifa Aulia Agustiana (Hutanasyah : Jurnal Hukum Tata Negara, 2025)
The implementation of the rule of law principle within Indonesia's decentralization policy is a strategic step toward establishing a more transparent, accountable, and responsive government to local needs. However, this principle faces various challenges, such as regulatory interpretation differences between the central and regional governments, limited legal capacity at the local level, and pervasive corruption practices. This study aims to evaluate the effectiveness of applying the rule of law principle in decentralization policies, identify existing obstacles, and propose policy recommendations for improvement. A descriptive-analytical approach was employed, gathering data through literature reviews, legal document analysis, and interviews with experts in law and local governance. The results indicate that while there has been progress in implementing the rule of law in regional governance, several obstacles still hinder its effectiveness, including limited legal capacity at the local level and weak oversight mechanisms. Policy recommendations include enhancing legal training at the regional level, regulatory harmonization between central and local governments, and strengthening oversight mechanisms. With these recommendations in place, it is expected that the rule of law will more effectively support decentralization policies and strengthen local governance in Indonesia.